Peningkatan Keterampilan Membaca Menggunakan Media Pembelajaran Wordwall pada Materi Puisi Kelas X - Khikmawati, Arina Nur; Ngatmini; Arisul Ulumuddin; Ika Sari Astarina (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
The quality of education in Indonesia is certainly not far from the learning that exists in schools. The existence of safe, comfortable and student-centered learning. Making the world of education more advanced and qualified. Therefore, here I do research. This study aims to see students in the process of learning poetry material. Of course, here we see an increase in reading skills using wordwall learning media in class X students at SMK N 8 Semarang. Using a classroom action research method with a qualitative and quantitative approach. This study involves students in carrying out the learning process. starting from identifying the meaning of poetry, characteristics of poetry, elements of poetry and the differences between poetry and short stories, elements of poetry, writing poetry and making poetry musicalization. Data were collected through observation, interviews, and evaluation of work results. The results of the study showed that students’ reading skills can increase significantly when using wordwall learning media. Students also showed increased activity and enthusiasm in learning. This study concludes that wordwall learning media can improve reading skills in poetry material for class X at SMK N 8 Semarang.